Estimating the numbers of pregnant women infected with Zika virus and infants with congenital microcephaly in Colombia, 2015–2017. Issue 6 (June 2018) - Adamski, Alys; Bertolli, Jeanne; Castañeda-Orjuela, Carlos; Devine, Owen J.; Johansson, Michael A.; Duarte, Maritza Adegnis Gonzalez; Farr, Sherry L.; Tinker, Sarah C.; Reyes, Marcela Maria Mercado; Tong, Van T.; Garcia, Oscar Eduardo Pacheco; Valencia, Diana; et al.
Summary: Background: Colombia experienced a Zika virus (ZIKV) outbreak in 2015–2016. To assist with planning for medical and supportive services for infants affected by prenatal ZIKV infection, we used a model to estimate the number of pregnant women infected with ZIKV and the number of infants with congenital microcephaly from August 2015 to August 2017. Methods: We used nationally reported cases of symptomatic ZIKV disease among pregnant women and information from the literature on the percent of asymptomatic infections to estimate the number of pregnant women with ZIKV infection occurring August 2015–December 2016. We then estimated the number of infants with congenital microcephaly expected to occur August 2015–August 2017. To compare to the observed counts of infants with congenital microcephaly due to all causes reported through the national birth defects surveillance system, the model was time limited to produce estimates for February–November 2016. Findings: We estimated 1140–2160 (interquartile range [IQR]) infants with congenital microcephaly in Colombia, during August 2015–August 2017, whereas 340–540 infants with congenital microcephaly would be expected in the absence of ZIKV. Based on the time limited version of the model, for February–November 2016, we estimated 650–1410 infants with congenital microcephaly in Colombia. The 95% uncertainty interval for the latter estimate encompasses the 476 infants with congenital microcephaly reported during that approximate time frame based on national birth defects surveillance. Interpretation: Based on modeled estimates, ZIKV infection during pregnancy in Colombia could lead to 3–4 times as many infants with congenital microcephaly in 2015–2017 as would have been expected in the absence of the ZIKV outbreak. Funding: This publication was made possible through support provided by the Bureau for Global Health, U.S. Agency for International Development under the terms of an Interagency Agreement with Centers for Disease Control and Prevention.